2021
DOI: 10.1111/php.13547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Serum Albumin on the Fluorescence Intensity and Tumor Imaging Properties of IR‐780 Dye

Abstract: IR‐780 is a lipophilic dye with excellent optical and tumor imaging properties for early tumor diagnostics. Although the mechanism of tumor targeting has not been fully identified, the view that serum albumin plays an important role in tumor accumulation has been recognized. Here, the mechanism of the interaction between IR‐780 and HSA was studied to explore the effect of albumin on its tumor targeting properties. Data demonstrate that IR‐780 can be tightly adsorbed by HSA at a ratio of 1:1 to form a noncovale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Studies also have shown the interaction of the IR-780 marker with other molecules in order to form stable nano-complexes or micelles with ability to selectively amplify cytotoxic activity in tumor cells. Some of these interactions can occur with organic compounds, such as albumin, with which it forms weak non-covalent binding [18,23,35,36]. This kind of bind explains fluorescence images in animals with no tumor cells (Figure 4), where non-fluorescence images were expected.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies also have shown the interaction of the IR-780 marker with other molecules in order to form stable nano-complexes or micelles with ability to selectively amplify cytotoxic activity in tumor cells. Some of these interactions can occur with organic compounds, such as albumin, with which it forms weak non-covalent binding [18,23,35,36]. This kind of bind explains fluorescence images in animals with no tumor cells (Figure 4), where non-fluorescence images were expected.…”
Section: Discussionmentioning
confidence: 93%
“…Plasma proteins also play an important role in the marker's uptake by tumor cells. IR-780 has the ability to form non-covalent complexes with plasma albumin, which enhances its fluorescence capacity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular Docking Simulation and Physicochemical Parameters Calculation: In this study, AutoDock software (version 4.0) was used to predict the binding sites of Cy7 dyes on HSA, as previously described. [41] Briefly, the 3D crystal structure of HSA (PDB ID: 1H9Z) was obtained from the RCSB Protein Data Bank, and the solvent molecules were removed using PyMOL before docking. The grid box parameters are based on previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…To date, IR780 has been applied to imaging various cancerous tissues, such as breast, cervical, lung, osteosarcoma, and prostate cancer tumors in mice [13,14]. Additionally, IR780 is widely used not only as a commercially available NIR contrast agent, but also as a photosensitizer for photothermal and photodynamic therapy, generating a temperature increase or reactive oxygen species after laser irradiation, respectively [15]. Zhang et al reported the basic properties and tumor targeting mechanisms of IR780 by CCD-based in vivo spectral (IVIS) imaging system, revealing the early diagnosis of tumors and sentinel lymph node mapping, which greatly promoted the development of IR780 [14].…”
mentioning
confidence: 99%